Quantifying mechanical and metabolic interdependence between speed and propulsive force during walking - Pimentel, Richard E.; Feldman, Jordan N.; Lewek, Michael D.; Franz, Jason R. (Frontiers in Sports and Active Living, 2022)
Walking speed is a useful surrogate for health status across the population. Walking speed appears to be governed in part by interlimb coordination between propulsive (FP) and braking (FB) forces generated during step-to-step transitions and is simultaneously optimized to minimize metabolic cost. Of those forces, FP generated during push-off has received significantly more attention as a contributor to walking performance. Our goal was to first establish empirical relations between FP and walking speed and then to quantify their effects on metabolic cost in young adults. To specifically address any link between FP and walking speed, we used a self-paced treadmill controller and real-time biofeedback to independently prescribe walking speed or FP across a range of condition intensities. Walking with larger and smaller FP led to instinctively faster and slower walking speeds, respectively, with 80% of variance in walking speed explained by FP. We also found that comparable changes in either FP or walking speed elicited predictable and relatively uniform changes in metabolic cost, together explaining 53% of the variance in net metabolic power and 14% of the variance in cost of transport. These results provide empirical data in support of an interdependent relation between FP and walking speed, building confidence that interventions designed to increase FP will translate to improved walking speed. Repeating this protocol in other populations may identify other relations that could inform the time course of gait decline due to age and disease.